. An Analysis of Mahmud Abu Rayyah’s Criticism on Abu Hurairah’s Credibility as a Hadith Narrator: Analisis Kritik Mahmud Abu Rayyah terhadap Kredibilitas Abu Hurairah sebagai Perawi Hadis - Nawawi, Ruston (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: This study aims at analyzing Mahmud Abu Rayyah's allegations against Abu Hurairah one of the leading transmitters of hadith as well as evaluating the validity of these allegations in hadith narration. Methodology: The study used a descriptive qualitative method with primary data from hadith books and secondary data from modern literature and scholarly journals. The analysis was done through the stages of verification, reduction, thematic arrangement, and interpretation of data. Main Results: The results show that Mahmud Abu Rayyah's accusations against Abu Hurairah are based on misinterpretation and lack of contextual understanding. Abu Hurairah, although only with the Prophet for about three years, played an important role in hadith narration. The traditions he narrated have been verified by scholars and accepted in the hadith literature. Involvement: This study reinforces Abu Hurairah's position as a credible narrator and highlights the importance of sanad and matan criticism methods in hadith verification. Conclusions: Abu Rayyah's allegations have proven to be unfounded and this study underscores the efforts of scholars in preserving the authenticity of hadith. Future research should include a broader perspective of schools of thought and explore the impact of hadith polemics on contemporary religious understanding and practice.